2013
DOI: 10.1159/000342533
|View full text |Cite
|
Sign up to set email alerts
|

Early Influences of Nutrition on Postnatal Growth

Abstract: Health and nutrition modulate postnatal growth. The availability of amino acids and energy, and insulin and insulin-like growth factor-I (IGF-I) regulates early growth through the mTOR pathway. Amino acids and glucose also stimulate the secretion of IGF-I and insulin. Postnatal growth induces lasting, programming effects on later body size and adiposity in animals and in human observational studies. Rapid weight gain in infancy and the first 2 years was shown to predict increased obesity risk in childhood and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 76 publications
1
34
0
1
Order By: Relevance
“…Accelerated postnatal weight gain can result from high intake of growth-enhancing nutrients such as protein in the infant diet. Available evidence suggests that higher protein intakes increase plasma and tissue levels of insulin-releasing amino acids and of insulin and insulinlike growth factor 1, and thereby increase weight gain and adipogenic activity (36,37) .…”
Section: Accelerated Postnatal Growth Hypothesismentioning
confidence: 99%
“…Accelerated postnatal weight gain can result from high intake of growth-enhancing nutrients such as protein in the infant diet. Available evidence suggests that higher protein intakes increase plasma and tissue levels of insulin-releasing amino acids and of insulin and insulinlike growth factor 1, and thereby increase weight gain and adipogenic activity (36,37) .…”
Section: Accelerated Postnatal Growth Hypothesismentioning
confidence: 99%
“…2,3 Maternal pre-pregnancy BMI (pBMI) is more strongly associated 62 with excessive fetal growth and birthweight than hyperglycemia. 4 Different mechanisms have been 63 discussed for this intergenerational cycle of obesity, including epigenetic modulations or in-utero changes 64 in the appetite control system, 4,5 which have been primarily investigated in animal models to date.…”
Section: Introduction 57mentioning
confidence: 99%
“…We hypothesized that breastfeeding protects through reducing weight gain velocity during early childhood, resulting from a different substrate supply with breastfeeding compared to feeding conventional infant formula, in particular the markedly lower protein content in human milk than in infant formula [22,23]. Indeed, rapid weight gain during the first 2 years of life is highly predictive of overweight at early school age [24], which was confirmed in numerous other studies: an increase in weight-for-age SD score >0.67 SD during the 1st and 2nd year of life predicts two- to threefold increased odds of obesity in children, teenagers and adults [25]. A recent systematic review and meta-analysis of 15 studies examining body composition in healthy infants showed that breastfed infants had a lower body fat mass at age 1 year than formula-fed infants [26].…”
Section: Infant Diet Early Growth and Later Obesitymentioning
confidence: 81%
“…We hypothesise that enhanced concentrations of branched-chain amino acids in response to protein supply may be causative for inducing excessive weight gain and higher body fat mass in formula-fed compared to breastfed subjects. Experimental observations provide support for a potential key role of amino acids in growth regulation [25]. Verification of this hypothesis would allow new avenues to early obesity prevention by modifying specifically the amino acid composition of feed, rather than reducing further the total protein intake, which has considerable limitations for practical and safety reasons.…”
Section: Metabolic Mechanismsmentioning
confidence: 99%